The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1038/tp.2013.89
|View full text |Cite
|
Sign up to set email alerts
|

Fear conditioning, persistence of disruptive behavior and psychopathic traits: an fMRI study

Abstract: Children diagnosed with Disruptive Behavior Disorders (DBD), especially those with psychopathic traits, are at risk of developing persistent and severe antisocial behavior. Deficient fear conditioning may be a key mechanism underlying persistence, and has been associated with altered regional brain function in adult antisocial populations. In this study, we investigated the associations between the neural correlates of fear conditioning, persistence of childhood-onset DBD during adolescence and psychopathic tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
57
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 50 publications
(65 reference statements)
4
57
0
Order By: Relevance
“…However, emotional hyporeactivity characterizes only one part of persistent offenders (Hodgins, 2007). Hyperreactivity during fear acquisition has been found in antisocial juveniles from lower social class (Raine and Venables, 1981) and in our previous fear acquisition study (Cohn et al, 2013). In summary, there is some evidence for aberrant fear responsiveness in subgroups of antisocial individuals, but the current literature on fear extinction in antisocial individuals is limited by an exclusive focus on the emotionally hyporeactive subgroup.…”
Section: Introductionmentioning
confidence: 49%
See 4 more Smart Citations
“…However, emotional hyporeactivity characterizes only one part of persistent offenders (Hodgins, 2007). Hyperreactivity during fear acquisition has been found in antisocial juveniles from lower social class (Raine and Venables, 1981) and in our previous fear acquisition study (Cohn et al, 2013). In summary, there is some evidence for aberrant fear responsiveness in subgroups of antisocial individuals, but the current literature on fear extinction in antisocial individuals is limited by an exclusive focus on the emotionally hyporeactive subgroup.…”
Section: Introductionmentioning
confidence: 49%
“…that its dimensions are distinctly associated with behavioral criterion variables (Patrick et al, 2005;Hicks and Patrick, 2006) and regional brain function (Carré et al, 2013;Cohn et al, 2013). Indeed, we found that neural responses during fear acquisition were positively associated with GM and II psychopathic traits and negatively with CU psychopathic traits (Cohn et al, 2013). However, nothing is known about the associations between the different psychopathic traits and brain activation during fear extinction.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations